TAXILA UNDER SIEGE: ANCIENT BATTLEFIELD BETWEEN INVADERS (HISTORICAL NOTES ON TAXILA’S INVASION) - Mohammad Kashif Faisal; Syed Hamid Mehmood Bukhari; Dr. Attiya Iqbal (`, 2025)
Taxila is an important city of Archaeological remains in the District of Rawalpindi in Punjab, it is an old city of considerable Archaeological and Historical heritage, housing important ancient landmarks. Taxila remains are the national assets of Pakistan and it is also one of the six world heritage of our country. Taxila is the land of ancient Buddhist civilization. The large number of Buddhist Monuments, Stupas, Monasteries and Temples are stands with dignity and these valuable remains spread In all over Taxila region around 30 kilometer in range. Taxila has its rich political history it was flourished city ever under many great periods and became an important and prominent battlefield between invaders. With the passage of time Taxila faced many invasions and it was the center of power and the land of attraction for Persians, Greeks under Alexander the great and Central Asian invaders. In this study I discussed the splendid era of ancient Taxila under great Kingdoms and different invasions. Taxila was not only historical center for the Buddhist civilization but also was the political and economic hub in ancient time Keywords:- Persians, Aryans, Achaemenids, Maurians, Greeks, Indo-Greeks, Scythians, Parthians, Kushans, Sassanids, Kedara Kushan, White Huns, Turk Shahis, Hindu Shais